The association between nonsteroidal anti-inflammatory drugs and skin cancer: Different responses in American and European populations. (February 2020) - Ma, Yukun; Yu, Piaojian; Lin, Shuhuang; Li, Qiqun; Fang, Zijing; Huang, Zunnan
Graphical abstract: Abstract: Objective: To conduct a comprehensive systematic meta-analysis investigating the association of nonsteroidal anti-inflammatory drugs (NSAIDs) and their subtypes with skin cancer (SC) and its subclasses (basal cell carcinoma BCC; squamous cell carcinoma SCC; melanoma; nonmelanoma skin cancer NMSC) in general, American and European populations. Methods: PubMed, Embase, the Cochrane Library, the China National Knowledge Infrastructure and ClinicalTrials.gov were searched up to 24 February 2019. Pooled effect sizes and 95% confidence intervals were used to estimate associations. Results: Results based on 26 original studies including 223, 619 cases and 1, 398, 507 controls showed both NSAIDs and nonselective Cyclooxygenase (COX) inhibitors to be statistically significantly associated with a reduced risk of SC, BCC, SCC and NMSC but not with melanoma. Conversely, no association was observed between selective Cyclooxygenase 2 (COX-2) inhibitors and SC or its subclasses. Further subgroup analysis showed that the results analyzed for American populations were almost the same as those for the general population. For European populations, neither NSAIDs nor its subtypes correlated significantly with susceptibility to SC or its subclasses. Conclusions: The use of NSAIDs might reduce the risk of SC, but many factors including study population, drug subtype, and disease subclass affect the significance of the association.